COMMON PROBLEMS WITH FRUIT DRYING INCLUDE THE FOLLOWING - Khaidarova Nargiza Dilmurod kizi; Sadullaev Shuhrat Narzulloyevich; Xamrayev Sunnatillo Abduxakimovich (European Science Publishing, 2024)
Product quality: Improper drying techniques can cause loss of product quality such as loss of taste, aroma and color. Yes, this is one of the main problems with drying fruits and vegetables. Improper drying techniques can lose the taste, aroma and color of the product, which reduces its quality and popularity among consumers. For example, drying at very high temperatures can cause the loss of vitamins and minerals, while drying in the sun causes the product to lose color and taste.
Keywords: Vacuum freeze-drying, vacuum sublimation method, optimal temperature.